Weight loss with real-world doravirine use in the OPERA cohort: a US-based cohort study - Karam Mounzer; Laurence Brunet; Michael Sension; Ricky K. Hsu; Michael D. Osterman; Jennifer S. Fusco; Yohance O. Whiteside; Gregory P. Fusco (AIDS Research and Therapy)
Abstract Background Weight gain has been associated with the use of antiretrovirals in people with HIV, especially with integrase inhibitors or tenofovir alafenamide, and among women. In 2018, doravirine became the latest non-nucleoside reverse transcriptase inhibitor to be approved in the US. We assessed changes in weight over time among virologically suppressed individuals who switched to a regimen containing doravirine (DOR). Methods From the US-based OPERA cohort, treatment-experienced adults with HIV who switched to a DOR-containing regimen between 30AUG2018-30NOV2022 with a viral load < 50 copies/mL were included (followed through 31MAY2023). The study population was characterized and a linear mixed model was used to estimate rates of weight change on DOR. Results were stratified by sex, by patterns of efavirenz (EFV) and/or tenofovir disoproxil fumarate (TDF) use before/after switch to DOR, and by integrase inhibitor (INSTI) & tenofovir alafenamide (TAF) use combination (restricted to individuals who maintained the same combination before/after switch). Results Of 388 included individuals, 21% were women, 33% were Black, and 78% were obese or overweight at DOR switch. Overall, people who switched to DOR lost an average of 0.80 kg/year (95% CI: -1.32, -0.28). Both women and men experienced statistically significant weight loss; women (70% Black, 70% aged ≥ 40 years) lost weight at a rate of -1.67 kg/year (95% CI: -3.32, -0.02) and men at a rate of -0.60 kg/year (95% CI: -1.12, -0.08). When EFV and TDF were absent before and after switch to DOR, statistically significant weight loss was observed. Among those who had the same INSTI and TAF combination throughout and had any INSTI or TAF use, a statistically non-significant trend toward weight loss was observed. Conclusions In one of the first real-world analyses of weight changes among virologically suppressed individuals who switched to a DOR-containing regimen in the US, DOR was associated with statistically significant weight loss. Patterns of use of other antiretrovirals did not fully explain the observed weight loss. These findings are clinically meaningful given that most individuals included were overweight or obese at switch to DOR and that women were predominantly of perimenopausal or menopausal age.